The era of increasing cancer survivorship: Trends in fertility preservation, medico-legal implications, and ethical challenges - De Paola Lina; Napoletano Gabriele; Gullo Giuseppe; Circosta Francesco; Montanari Vergallo Gianluca; Marinelli Susanna (Open Medicine)
Global cancer cases are increasing, but fortunately, cancer is becoming more treatable. By 2050, the number of cancer cases is projected to reach 35 million. These numbers are certainly correlated with the aging population, early diagnoses due to screenings, and the broad current treatment options. However, life-saving therapies are often gonadotoxic, significantly impacting the lives of cancer patients. Fertility preservation following life-saving oncological treatments is one of the challenges faced by patients with cancer.